2023
DOI: 10.3390/nano13192684
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Functions of Carbon Dots and Their Applications in Agriculture: A Review

Guohui Li,
Jiwei Xu,
Ke Xu

Abstract: Carbon dots are carbon-based nanoparticles, which have the characteristics of a simple preparation process, photoluminescence, biocompatibility, an adjustable surface function, water solubility, and low-level toxicity. They are widely used in biological applications, such as imaging, biosensing, photocatalysis, and molecular transfer. They have also aroused great interest among researchers in agriculture, and there has been significant progress in improving crop growth and production. This review presents the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…It can be observed that Ce, CDs, and Ce-CDs can promote the growth and development of lettuce compared to the blank control group. 53 As compared to the control group, the 100 mg L −1 Ce treatment results in 20.3, 21.9, 33, and 9.8% increase in fresh weight, dry weight, soluble sugar content, and soluble protein content of lettuce plants, respectively. The 100 mg L −1 CD treatment increases these indices by 26, 24.1, 30.4, and 17.3%, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…It can be observed that Ce, CDs, and Ce-CDs can promote the growth and development of lettuce compared to the blank control group. 53 As compared to the control group, the 100 mg L −1 Ce treatment results in 20.3, 21.9, 33, and 9.8% increase in fresh weight, dry weight, soluble sugar content, and soluble protein content of lettuce plants, respectively. The 100 mg L −1 CD treatment increases these indices by 26, 24.1, 30.4, and 17.3%, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Due to the nanometric size of carbon dots (CD), they enter plants by root and leaf absorption and may interfere with the plant's physiology (Figure 5) [27]. CD will increase the crop yield by enhancing plant photosynthesis, acting as nanofertilizers, promoting good seed germination by facilitating water absorption, improving plants' resistance to abiotic stress, and inactivating toxic pollutants [27]. Carbon nanomaterials have another important role in agricultural practices, namely as nanocarriers for pesticides and fertilizers, allowing the controlled release of active molecules [20].…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%